Potentiation of Sodium Metabisulfite Toxicity by Propylene Glycol in Both in Vitro and in Vivo Systems - Yoo, Jean; Lim, Yeon-Mi; Kim, Haewon; Kim, Eun-Ji; Lee, Doo-Hee; Lee, Byeongwoo; Kim, Pilje; Yu, Seung Do; Kim, Hyun-Mi; Yoon, Byung-Il; Shim, Ilseob (Frontiers in Pharmacology, 2018)
Many consumer products used in our daily lives result in inhalation exposure to a variety of chemicals, although the toxicities of the active ingredients are not well known; furthermore, simultaneous exposure to chemical mixtures occur. Sodium metabisulfite (SM) and propylene glycol (PG) are used in a variety of products. Both the cytotoxicity and the sub-acute inhalation toxicity of each chemical and their mixtures were evaluated. Assays for cell viability, membrane damage, and lysosome damage demonstrated that SM over 100 μg/mL induced significant cytotoxicity; moreover, when PG, which was not cytotoxic, was mixed with SM, the cytotoxicity of the mixture enhanced. Solutions of 1%, 5%, and 20% SM, each with 1% PG solution, were prepared, and the whole body of rats was exposed to aerosols of the mixture for 6 h/day, 5 days/week for 2 weeks. The rats were sacrificed 1 day (exposure group) or 7 days (recovery group) after termination of the exposure. The actual concentration of SM in the low-, medium-, and high-exposure groups was 3.91 ± 1.26, 35.73 ± 6.01, and 80.98 ± 5.47 mg/m3, respectively, and the actual concentration of PG in each group was 6.47 ± 1.25, 8.68 ± 0.6, and 8.84 ± 1.77 mg/m3. The repeated exposure to SM and PG caused specific clinical signs including nasal sound, sneeze and eye irritation which were not found in SM single exposure. In addition, the body weight of treatment group rats decreased compared to that of the control group rats in a time-dependent manner. The total protein (TP) concentration and lactate dehydrogenase activity in the bronchoalveolar lavage fluid (BALF) increased. Histopathological analysis of the lungs, liver, and nasal cavity was performed. Adverse effects were observed in the nasal cavity, with squamous cell metaplasia identified in the front of the nasal cavity in all high-exposure groups, which completely recovered 7 days after exposure was terminated. Whereas inhalation of SM for 2 weeks only reduced body weight in the high-dose group, inhalation of SM and PG mixtures for 2 weeks significantly decreased body weight and induced metaplasia of the respiratory epithelium in squamous cells in the medium- and high-dose